(untitled) (Communications in Computational Physics, 2014)
The singularity of specific heat CV of the three-dimensional Ising model is studied based on Monte Carlo data for lattice sizes L≤1536. Fits of two data sets, one corresponding to certain value of the Binder cumulant and the other — to the maximum of CV, provide consistent values of C0 in the ansatz CV (L) =C0+ALα/ν at large L, if α/ν = 0.196(6). However, a direct estimation from our C^max_V data suggests that α/ν, most probably, has a smaller value (e.g., α/ν=0.113(30)). Thus, the conventional power-law scaling ansatz can be questioned because of this inconsistency. We have found that the data are well described by certain logarithmic ansatz.